Komunikasi Dakwah Ustadz Hilal Hamdi di Pondok Pesantren Nurul Hikmah - Iis Anugrah Rahmat Hidayatullah (Prodi Komunikasi & Penyiaran Islam, Program Pascasarajana, UIN Sunan Gunung Djati Bandung, 2018)
Da'wah communication is a branch of communication science that is essential for da’i in delivering messages effectively. Ustadz Hilal Hamdi, as a dormitory supervisor at Pondok Pesantren Nurul Hikamah, strives to apply da'wah communication principles in guiding his students. This study examines the methods he employs in da'wah and his approach to upholding Islamic teachings. The findings indicate that he emphasizes an interpersonal psychological approach and provides direct examples of the knowledge taught. It is recommended that special attention be given to students to prevent rule violations and that a counseling body be established to address students' issues in the dormitory.